2021
DOI: 10.1016/j.scitotenv.2021.145796
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of mercury in the mesopelagic domain of the Pacific and Atlantic oceans using body feathers of Bulwer's petrel as a bioindicator

Abstract: Bulwer's petrels were used as biomonitors of Hg levels in the mesopelagic domain.• Atlantic colonies showed higher Hg concentrations than those from the Pacific. • CSIA-AA-derived trophic levels for chicks were similar among colonies. • Feather Hg levels recorded were lower than those reported in 1992 for the Atlantic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…The chicks of White-faced Storm Petrel showed no significant differences in mercury concentration in body feathers compared to the chicks of Bulwer's Petrel, a specialist predator of mesopelagic prey (Waap et al 2017) from the Deserta Grande, Madeira (275 km north of our study site), that showed a mercury concentration in body feathers of 4.38 ± 1.69 mg kg −1 dw in 2018 (mean ± SE, Furtado et al 2021) (Welch's t test, t = − 1.491, df = 0.28, P = 0.148). Seabirds feeding on mesopelagic prey present higher mercury concentrations in feathers than those feeding predominantly on epipelagic prey (Monteiro and Furness 1995;Kim et al 1996;Monteiro et al 1996;Bond and Diamond 2009;Carravieri et al 2018;Furtado et al 2019Furtado et al , 2021. Hence, mercury measurements in feathers support the idea that White-faced Storm Petrels raise their chicks mostly on mesopelagic prey.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…The chicks of White-faced Storm Petrel showed no significant differences in mercury concentration in body feathers compared to the chicks of Bulwer's Petrel, a specialist predator of mesopelagic prey (Waap et al 2017) from the Deserta Grande, Madeira (275 km north of our study site), that showed a mercury concentration in body feathers of 4.38 ± 1.69 mg kg −1 dw in 2018 (mean ± SE, Furtado et al 2021) (Welch's t test, t = − 1.491, df = 0.28, P = 0.148). Seabirds feeding on mesopelagic prey present higher mercury concentrations in feathers than those feeding predominantly on epipelagic prey (Monteiro and Furness 1995;Kim et al 1996;Monteiro et al 1996;Bond and Diamond 2009;Carravieri et al 2018;Furtado et al 2019Furtado et al , 2021. Hence, mercury measurements in feathers support the idea that White-faced Storm Petrels raise their chicks mostly on mesopelagic prey.…”
Section: Discussionmentioning
confidence: 60%
“…Feathers were clipped at the superior umbilicus of the feather, excluding the calamus, and stored in polyethylene bags. Samples were weighed on a Sartorius M5P micro balance (Sartorius AG, Goettingen) (mass between 0.441 and 3.020 mg, mean 1.23 ± 0.59 mg) and analysed according to the method described in Furtado et al (2021). Total mercury in the body feathers was quantified by atomic absorption spectrophotometry with thermal decomposition (Costley et al 2000) in LECO AMA-254 with a detection limit of 0.01 ng of mercury.…”
Section: Mercury Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Other marine organisms such as sea birds have also been shown to reflect regional characteristics on Hg levels. Comparing 2 colonies of Bulwer's petrel Bulweria bulwerii between the Atlantic and the Pacific showed that chicks and adults had significantly higher concentrations of Hg in the colonies of the Atlantic than those of the Pacific Ocean (Furtado et al 2021). Given that this species has no apparent trophic differences, the most likely explanation is that food items consumed by these birds (e.g.…”
Section: Discussionmentioning
confidence: 99%